A prospective observational study of adverse drug reactions to antiretroviral therapy: type and risk factors in a tertiary care teaching hospital - Bhuvana, K. B.; Hema, N. G.; ., Sangeetha (International Journal of Basic & Clinical Pharmacology, 2017)
Background: To collect demographic details of patients receiving antiretroviral therapy (ART) and study type of adverse drug reactions (ADRs) and risk factors for ADRs to ART and to assess causality, severity, and preventability assessment of the reported ADRs. Methods: A prospective observational study was conducted for 6 months from January 2012 until June 2012 at ART Center, KR Hospital of Mysore Medical College & Research Institute, Mysore. Data were evaluated for patient demography, risk factors for ADRs, type of ADRs. ADRs were also assessed for their causality, severity, and preventability as per the standard algorithm, using SPSS for windows (version 16.0). Results: Out of 158 patients evaluated, majority were of age group of 21-40 years (66.5%). More number of illiterate patients (55.7%) showed ADRs to ART. Most patients were of CD4 count <250 cells/μl (65.82%). Most common regimen which caused ADRs was zidovudine + lamivudine + nevirapine. Most common type of ADRs was anemia (55.06%) and rash (25.31%). On evaluation of the causality of ADRs, majority were found to be possible (89.24%). The severity assessment showed that most of the patients ADRs were of level 3 (93.05%). The preventability assessment showed that 30.38% patients ADRs were preventable. Conclusion: Identifying risk factors are of crucial importance to optimize the initial choice of ARVs regimen before initiating therapy and to prevent severity and complications caused by ART, thereby improving the quality of care to patients on ART.